EFEKTIVITAS PROGRAM PENCEGAHAN STUNTING DI UPT PUSKESMAS KOMBO KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - ABDUL HAMID; RACHMAD (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the effectiveness of the Stunting Prevention Program at the Kombo Community Health Center, South Dampal District, Tolitoli Regency. The basis of this research is descriptive qualitative with a total of 9 informants. Data and material collection was carried out through informants accompanied by observation, interviews and documentation. The theory used in this research is Richard M. Steers (1985-53), which includes: (1) Goal Achievement (2) Integration, (3) Adaptation. Data analysis used in this research includes data collection, data reduction, data presentation, drawing conclusions. The results of this research indicate that the Stunting Prevention Program at the UPT Puskesmas Kombo, Dampal Selatan District, Tolitoli Regency is quite effective in terms of achieving goals, integration and adaptation. However, in the process of the stunting prevention program, obstacles are still found, namely mothers of toddlers who experience stunting are not diligent in attending posyandu, mothers have limited knowledge regarding correct child rearing patterns and providing nutritious food, the condition of children who have difficulty eating and the lack of clean water for consumption and mothers Stunted toddlers are less able to grasp socialization material quickly due to limited knowledge.